Artikulasi Islam Nusantara dalam Perjuangan Agraria - Mohamad Shohibuddin (Faculty of Islam Nusantara University of Nahdlatul Ulama Indonesia (UNUSIA) Jakarta., 2020)
This article focuses on a specific topics rarely discussed in the scholarship of Islam Nusantara, namely the contribution of Islam Nusantara in addressing agrarian problems experienced by the community. To disclose such contribution, the author proposes the perspective of “access and exclusion” as a theoritical framework for understanding the nature of social struggle in the agrarian field. Based on this, the author will disclose the contribution of Islam Nusantara in “pursuing access” and at the same token “preventing exclusion” within various situations of agrarian struggle, starting from the family level (as concerned with inheritance system and joint marital property) to broader level of socio-agrarian relations (as related to inequalities in land tenure, relations of production and spatial allocation). In addition, the author will examines “agrarian ijtihad” issued by Nahdlatul Ulama and also proposes the idea of “agrarian waqf”—both constitute religious responses to “challenges of access” and “threats of exclusion” taking place within the community. Keywords: Islam Nusantara, struggle for access; struggle against exclusion; agrarian ijtihad; Nahdlatul Ulama; agrarian waqf Reference Abbasi, Muhammad Zubair, “The Classical Islamic Law of Waqf: A Concise Introduction.” Arab Law Quarterly 26, No. 2 (2012): p. 121-153. Abu Zahrah, Muhammad, Muhâdlarât fî al-Waqf. Tanpa tempat terbit: Ahmad ’Ali Mukhaymar, 1959. Hall, Derek, Philip Hirsch, Tania Murray Li, Powers of Exclusion: Land Dilemmas in Southeast Asia. Singapore: NUS Press, 2011. Ibrahim, Bilal, “Beyond State and Peasant: The Egalitarian Import of Juristic Revisions of Agrarian and Administrative Contracts in the Early Mamlūk Period.” Islamic Law and Society 16, No. 3-4 (2009): p. 337-382. Johansen, Baber, The Islamic Law on Land Tax and Rent: The Peasants’ Loss of Property Rights as Interpreted in the Hanafite Legal Literature of the Mamluk and Ottoman Periods. London, New York, Sydney: Croom Helm, 1988. Lembaga Ta'lif wan Nasyr PWNU Jawa Timur, Ahkamul Fuqaha: Solusi Problematika Aktual Hukum Islam. Keputusan Muktamar, Munas dan Konbes Nahdlatul Ulama (1926-2004). Surabaya: Khalista, 2007. Luthfi, Ahmad Nashih, “Sejarah dan Revitalisasi Perjuangan Pertanian Nahdlatul Ulama Melawan Ketidakadilan Agraria.” Bhumi: Jurnal Agraria Dan Pertanahan 3, No. 2 (2017): p. 145-159. Megawati Institute,Hasil Riset Oligarki Ekonomi. Jakarta: Megawati Institute, 2017. Powers, David S., “Orientalism, Colonialism, and Legal History: The Attack on Muslim Family Endowments in Algeria and India.” Comparative Studies in Society and History 31, No. 3 (1989): p. 535-571. Ribot, Jesse C. and Nancy Lee Peluso, “A Theory of Access.” Rural Sociology 68 No. 2 (2003): p. 153-181. Shohibuddin, Mohamad, Eko Cahyono, Adi Dzikrullah Bahri, “Undang-Undang Desa dan Isu Sumber Daya Alam: Peluang Akses atau Ancaman Eksklusi?” Wacana 19, No. 36 (2017): p. 29-81. Tersedia melalui tautan berikut ini: http://ipb.link/desa-dan-agraria. Shohibuddin, Mohamad, Ahmad Nashih Luthfi, Westi Utami, ed. Meninjau Ulang Pengaturan Hak Adat. Yogyakarta dan Bogor: STPN Press dan Pusat Studi Agraria IPB, 2019. Bisa diunduh melalui tautan berikut: http://bit.ly/36pdY5e. Shohibuddin, Mohamad dan Adi D. Bahri, ed. Perjuangan Keadilan Agraria. Yogyakarta, Bogor, Jakarta dan Bandung: Insist Press bekerja sama dengan Sajogyo Institute, Bina Desa dan Akatiga, 2019. Pengantar penyunting dapat dilihat melalui tautan ini: http://bit.ly/2QR2jaK. Shohibuddin, Mohamad, “Dua Wajah Islam Nusantara.” Koran Sindo, 11 April 2017. Versi lebih panjang dapat dilihat pada tautan ini: https://www.facebook.com/notes/mohamad-shohibuddin/dua-wajah-islam-nusantara/10155013669631224. ———-, Perspektif Agraria Kritis: Teori, Kebijakan dan Kajian Empiris. Yogyakarta: STPN Press, PSA IPB, Sajogyo Institute dan KPA, 2018. Bisa diunduh melalui tautan berikut ini: http://ipb.link/perspektif-agraria. ———-, Wakaf Agraria: Signifikansi Wakaf Bagi Agenda Reforma Agraria. Yogyakarta dan Bogor: Baitul Hikmah, Magnum Pustaka Utama dan Sajogyo Institute, 2019. Beberapa review buku ini bisa dilihat pada tautan ini: http://bit.ly/2NLwyxp. ———-, “Mempertimbangkan Wakaf Sebagai Skema Alternatif Pelaksanaan Tenure Reform.” Dalam Mohamad Shohibuddin dan Adi D. Bahri, ed. Perjuangan Keadilan Agraria. Yogyakarta, Bogor, Jakarta dan Bandung: Insist Press bekerja sama dengan Sajogyo Institute, Bina Desa dan Akatiga, 2019. Bab ini bisa diunduh melalui tautan berikut ini: http://bit.ly/2PI0omw. ———-, “Wakaf Berjangka untuk Pembaruan Tenurial Skala Desa.” Dalam Adi D. Bahri dan Mohamad Shohibuddin, ed. Perjuangan Keadilan Agraria: Inspirasi Gunawan Wiradi. Bogor, Bandung, Jakarta, Yogyakarta: Sajogyo Institute, PSA IPB, Akatiga, Bina Desa, STPN Press, 2020. Bisa diunduh melalui tautan ini: https://ipb.link/wakaf-berjangka. ———-, Ketimpangan Agraria di Indonesia: Pendekatan Studi, Kondisi Terkini dan Kebijakan Penanganan. Bogor: IPB Press, 2020. Versi e-book bisa diperoleh melalui tautan berikut ini: http://bit.ly/BukuKetimpanganAgraria. Winoto, Joyo, “Reforma Agraria: Mandat Politik, Konstitusi dan Hukum dalam Rangka Mewujudkan Tanah untuk Keadilan dan Kesejahteraan Rakyat.” Kuliah Umum disampaikan di Balai Senat Universitas Gadjah Mada, Yogyakarta pada 22 November 2007.